Analysis of influencing factors of the efficacy of endoscopic dacryocystorhinostomy - YAO Yuejiao; MO Ya (Yanke Xuebao)
[Objective:] To analyze the influencing factors for effect of endoscopic dacryocystorhinostomy. [Methods] A total of 90 patients (90 eyes) diagnosed with unilateral chronic dacryocystitis undergoing endoscopic dacryocystorhinostomy in the Department of ophthalmology, Hospital of Chengdu University of Traditional Chinese Medicine from January 2021 to July 2023 were included. All patients underwent lacrimal duct CT imaging and endoscopic dacryocystorhinostomy, and were followed up for 6 months to evaluate the efficacy of surgery. [Results] This study showed that 90% of patients with chronic dacryocystitis were female, and the average age of patients was (49.97±13.096) years. The results of univariate analysis showed that there was a correlation between intraoperative drainage tube placement and inferior turbinate hypertrophy and the efficacy of En-DCR (P<0.05). The results of Logistic regression analysis showed that inferior turbinate hypertrophy was a risk factor for the efficacy of En-DCR (P<0.05). [Conclusions] Dacryocystitis mostly occurs in middle-aged and elderly women. Inferior turbinate hypertrophy are the influencing factors of surgical effect. Chronic dacryocystitis mostly occurs in middle-aged and elderly women. Inferior turbinate hypertrophy is a risk factor affecting the curative effect of En-DCR surgery.